The Conceptual Component of the Concept of "Health" in English Linguacultures - Maxmudova Aziza (Scientific Trends, 2024)
The concept of «health» comprises complex structured mental formations that include notional, figurative, and value features, partially coinciding and differing in various linguocultures. The paper contains an analysis of origin of the word «health» in linguistic branches of Indo-European stem. It is found that the origin and meaning of the word «sog`lik» (health), fixed in the Uzbek language, is older, than the meaning of health as an «integrity of all systems of the organism», fixed in the Roman and Germanic linguistic branches. Health is a lasting value of universal type, but the content and actualization of peculiar features of the concept is different.
Keywords: Concept, health, state of the body, sog`lik, conceptual, linguoculture.